Desmosomal dysfunction due to mutations in desmoplakin causes arrhythmogenic right ventricular dysplasia/cardiomyopathy. - Yang, Zhao; Bowles, Neil E; Steven E Scherer; Taylor, Michael D; Kearney, Debra L; Ge, Shuping; Nadvoretskiy, Vyacheslav V; DeFreitas, Gilberto; Carabello, Blasé; Brandon, Lois I; Godsel, Lisa M; Green, Kathleen J; et al. (Circ Res, 2006)
Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is characterized by progressive degeneration of the right ventricular myocardium, ventricular arrhythmias, fibrous-fatty replacement, and increased risk of sudden death. Mutations in 6 genes, including 4 encoding desmosomal proteins (Junctional plakoglobin (JUP), Desmoplakin (DSP), Plakophilin 2, and Desmoglein 2), have been identified in patients with ARVD/C. Mutation analysis of 66 probands identified 4 variants in DSP; V30M, Q90R, W233X, and R2834H. To establish a cause and effect relationship between those DSP missense mutations and ARVD/C, we performed in vitro and in vivo analyses of the mutated proteins. Unlike wild-type (WT) DSP, the N-terminal mutants (V30M and Q90R) failed to localize to the cell membrane in desomosome-forming cell line and failed to bind to and coimmunoprecipitate JUP. Multiple attempts to generate N-terminal DSP (V30M and Q90R) cardiac-specific transgenes have failed: analysis of embryos revealed evidence of profound ventricular dilation, which likely resulted in embryonic lethality. We were able to develop transgenic (Tg) mice with cardiac-restricted overexpression of the C-terminal mutant (R2834H) or WT DSP. Whereas mice overexpressing WT DSP had no detectable histologic, morphological, or functional cardiac changes, the R2834H-Tg mice had increased cardiomyocyte apoptosis, cardiac fibrosis, and lipid accumulation, along with ventricular enlargement and cardiac dysfunction in both ventricles. These mice also displayed interruption of DSP-desmin interaction at intercalated discs (IDs) and marked ultra-structural changes of IDs. These data suggest DSP expression in cardiomyocytes is crucial for maintaining cardiac tissue integrity, and DSP abnormalities result in ARVD/C by cardiomyocyte death, changes in lipid metabolism, and defects in cardiac development.
Keywords: Animals; Apoptosis; Arrhythmogenic Right Ventricular Dysplasia; Cardiomyopathies; Cell Communication; Cell Line, Tumor; Desmoplakins; Desmosomes; DNA Mutational Analysis; Embryo, Mammalian; Heart; Humans; Intercellular Junctions; Lipid Metabolism; Mice; Mice, Transgenic; Mutation, Missense; Myocytes, Cardiac